Research Progress on Structural Properties of Casein Micelles and Their Application in Delivery Systems - YE Jingying, WU Fan, ZHANG Zhaoyue, WEN Xin, NI Yuanying, LI Mo (Shipin Kexue, 2025)
Milk is considered an important source of protein in human diets. As the major protein component in milk, casein has attracted extensive attention from scholars due to its biparental structure and self-assembly properties. However, the poor pH, Ca2+, and temperature stability of casein micelles limit their application in delivery systems. This article systematically introduces the structural types of casein, the methods for its structural analysis, the methods for its modification based on the defects of micelle properties and their subsequent applications, aiming to prove the huge potential of casein micelles as delivery systems for bioactive compounds. Furthermore, this review provides an outlook on the future development of casein micelle systems in the field of functional food ingredients.